Shattering Glass – Multimodal Lifestyle Homoeopathic Intervention for Weight Control (Homoeopathy for All, 2023)
Overweight and obesity is a  serious medical condition that  affects children and adolescents. Overweight is defined as having  excess body weight for a particular  height from fat, muscle, bone, water,  or a combination of these factors.  This article provides an overview  of the aetiology, diagnosis, and  WHO Classification of over Weight appropriate general & homoeopathic  management for controlling the  weight.